The influences of pulse exposure versus continuous exposure to cadmium are different: Mechanisms elucidated from motor behavior and brain in amphibian larvae - Minyi Huang; Jiawei Yin; Yuyue Wan; Renyan Duan (Ecotoxicology and Environmental Safety)
Cadmium (Cd) is a common environmental pollutant in aquatic ecosystems, often present in the form of pulses. However, the toxic effects of Cd on aquatic animals have been found to come primarily from continuous exposure, and there is little research on the effects of pulse exposure on animals. Here, the different effects of Cd exposure patterns on the motor behavior, brain histology and brain metabolism of Pelophylax nigromaculatus tadpoles (20 per parallel group) were explored. Our study showed that both continuous (CECd) and pulse exposure of Cd (PECd) led to a significant reduction in the moving distance (57.7 % vs 42.5 %), average speed (57.7 % vs 42.6 %) and moving frequency (45.3 % vs 7.9 %). Furthermore, both CECd and PECd led to the expansion and enlargement of the perivascular space of the cerebrum. Cd exposure increased the blood-brain barrier permeability, leading to brain cell swelling, and destroyed brain granular cells, Purkinje cells and brain gliacytes. Non-targeted metabolomics found a significant effect of Cd exposure on nucleic acid and amino acid metabolism. The most significant increases were observed in adenosine (99.4 %), threonine (47.9 %), citrulline (123.9 %), and erythrose 4p (184.1 %). It is noteworthy that the CECd exerted a more pronounced influence on brain structure, metabolism, and movement behaviour than the PECd. This phenomenon can be attributed to the fact that in PECd exposure, the individual's intermittent exposure to clean water partially offsets the effects of previous Cd exposure.